2019
DOI: 10.3390/polym11010167
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Organic Thermoelectric Materials: Principle Mechanisms and Emerging Carbon-Based Green Energy Materials

Abstract: Thermoelectric devices have recently attracted considerable interest owing to their unique ability of converting heat to electrical energy in an environmentally efficient manner. These devices are promising as alternative power generators for harvesting electrical energy compared to conventional batteries. Inorganic crystalline semiconductors have dominated the thermoelectric material fields; however, their application has been restricted by their intrinsic high toxicity, fragility, and high cost. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 166 publications
(158 reference statements)
1
79
0
Order By: Relevance
“…Organic materials including polyaniline (PANi), poly‐(3,4‐ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS), polypyrrole (PPy), and polyacetylene (PA) with a low thermal conductivity that are lightweight and flexible are widely studied as TMs . These organic TMs demonstrated advantages for assembling flexible TEG devices, but their low Seebeck coefficient and low electrical conductivity resulted in poor ZT values as well as lower power factors than those of inorganic TMs, which limits their applications.…”
Section: Materials For Energy Conversion Devicesmentioning
confidence: 99%
“…Organic materials including polyaniline (PANi), poly‐(3,4‐ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS), polypyrrole (PPy), and polyacetylene (PA) with a low thermal conductivity that are lightweight and flexible are widely studied as TMs . These organic TMs demonstrated advantages for assembling flexible TEG devices, but their low Seebeck coefficient and low electrical conductivity resulted in poor ZT values as well as lower power factors than those of inorganic TMs, which limits their applications.…”
Section: Materials For Energy Conversion Devicesmentioning
confidence: 99%
“…The TC, in the two directions, show a converse tendency with an increase in GF content, and apparently the composites exhibit obviously anisotropic characteristics. It is easy to understand of this converse tendency, since the GF possesses a higher intrinsic TC than Cu matrix in the X-Y plane, but a lower intrinsic TC than Cu matrix in the Z direction [32,33]. However, the TiC-coated graphite flake/Cu composites exhibit lower TC than the uncoated one, which can be attributed to two reasons.…”
Section: Bending Strengthmentioning
confidence: 99%
“…Since the mean lifetime of radicals in polymerization reactions becomes longer and termination reactions are delayed, the chain length and orientation of the polymer chains synthesized under MF are expected to increase. It has been explained theoretically as well as experimentally that carrier mobility and consequently electrical conductivity is increased by molecular weights of the conductive polymers [14,15,26]. It was reported that the polymers synthesized in an external MF demonstrate increased thermal stability and lower swelling due to their regulated structures.…”
Section: Introductionmentioning
confidence: 99%